Strategy to Increase the Competitiveness of MSME Businesses in the Era of Digitalization for Rural Communities in the Medan Region of North Sumatra - Salsabila, Anindiya; Adiza, Tengku Narasiya; Irdianti, Ananda Jaya; Saraswati , Dwi (Jurnal Pemberdayaan Ekonomi dan Masyarakat, 2024)
The era of digitalization presents opportunities and challenges for Micro, Small and Medium Enterprises (MSMEs) in rural areas. To increase competitiveness in this era, an appropriate and comprehensive strategy is needed. This abstract discusses strategies that can be implemented to increase the competitiveness of MSMEs in rural areas, with a focus on aspects of using digital technology to reach wider markets, increase operational efficiency, and build brand image. This can be done through the use of social media, e-commerce and other digital platforms to market products and services. Use of online accounting and bookkeeping applications to manage finances more effectively. The research method used is a qualitative method by collecting interviews, observing challenges and opportunities in the era of digitalization in the North Sumatra region. By using digital technology, increasing human resource capacity, strengthening networks and collaboration, and getting conducive infrastructure and policy support, MSMEs in rural areas can develop and contribute to the national economy.